Mothers’ perception of husband support during breastfeeding: A qualitative study in Indonesia - Mardiyaningsih, Eko; Widyawati, Widyawati; Hapsari, Elsi D. (Narra Sains Indonesia, 2024)
The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted maternal and perinatal healthcare worldwide, including in Indonesia. Restrictions on access to health services have forced mothers to adapt to new challenges in breastfeeding during the pandemic. The aim of this study was to evaluate mothers’ breastfeeding experiences and the role of husbands in providing support during this period. This qualitative research used a phenomenological approach. Data were collected from August to October 2022 through a focus group discussion (FGD). Participants were selected using maximum variation sampling, with eight mothers participating in the FGD. Data were analyzed using qualitative content analysis, revealing four main themes: (1) not all husbands fully supported mothers’ efforts to provide exclusive breastfeeding; (2) supportive and inhibiting factors help to provide exclusive breastfeeding; (3) mothers understood the benefits and identified the causes of failure in providing exclusive breastfeeding and complementary food for breast milk; and (4) various stressors experienced by mothers did not impede breastfeeding efforts. In conclusion, the findings highlight the need for healthcare workers, especially maternity nurses, to encourage continued breastfeeding and emphasize the importance of husbands’ support in providing exclusive breastfeeding initiatives. Interventions should be designed to actively involve husbands in supporting exclusive breastfeeding practices.